Research on Stability of Utralong and Deep-Buried Tunnel Surrounding Rocks Based on GA-GRNN Geostress Field Inversion - GUO Chong; WANG Hansheng; DENG Weijie; ZHAO Shunli; DU Weichang (Renmin Zhujiang)
According to the geological condition and measured geostress data of the utralong-distance water diversion project,a 3D inversion calculation model of the initial geostress field of the water diversion route was established.The initial geostress field of the water diversion route was exactly simulated through the method of generalized regression neural network (GRNN) optimized by genetic algorithms (GA-GRNN).Based on the initial geostress field,the geostress of the water diversion route was partitioned,and the stability of the tunnel surrounding rocks in typical sections was analyzed.The research results show that the geostress field is bounded by Duolong gully fault belt,and the west of the fault belt is a horizontal tectonic stress area.Extremely high and high geostress areas are distributed in geological structural belts where attention should be paid to rock bursts caused by stress release.The east of the Duolong gully fault belt is the self-weight stress area,and the moderate geostress area is distributed here.The stability of the surrounding rocks here is relatively good.